‘HOW MUCH SPACE AM I SUPPOSED TO TAKE?’: UNDERSTANDING ’DIGITAL INCLUSION FOR INTERNATIONAL DEVELOPMENT’ THROUGH FA’ASAMOA - Hourigan, Aimee (AoIR Selected Papers of Internet Research, 2023)
It is widely held that efforts to achieve the United Nations’ 2030 Sustainable Development Goals must sit alongside efforts to achieve ‘universal’ digital inclusion (Graham, 2019). In Samoa, an independent island state in the Pacific, digital inclusion has been positioned as a key ‘international development’ agenda that will ‘leapfrog’ the nation into the 21st century. However, a similarly strong motivator has been fa’asamoa (the Samoan way) which, with its emphasis on relationally grounded action and knowledges, operates in tension with the underlying colonial constructs of ‘modernity’ evident within current ’Western’ conceptualisations of ‘digital inclusion for international development’. In following Mignolo (2007), this paper details fa’asamoa-grounded perceptions and experiences of ‘digital inclusion for international development’ held by Samoan members of two Pasifika-led community organisations in Brisbane, Australia. The ’participants’, as peer researchers, held a central position in designing and implementing the research agenda and objectives, further putting abstract conceptualisations of decolonisation into practice. Drawing on discussions and design artefacts created during a co-design workshop held in late-2021, this paper outlines how the peer researchers (consciously and unconsciously) navigate tensions between fa’asamoa and current ’Western’ structures and practices of ‘digital inclusion for international development’ in their everyday and envisioned engagement with ICTs and digital technologies. In turn, this paper critically questions the effects of on-going ’Western’ hegemonies in the construction of ‘modern’ subjectivities and the enactment of ‘modern’ life, and further offers critical insight into the role of technology in the discursive and practical conception of alternatives to ‘modernity/coloniality’.